The Role of Perceived Organizational Support and Job Satisfaction on Work Engagement at PT. X - Widad Pratiwi; Hendro Prabowo (Jurnal Psikologi, 2025)
This study aims to determine the role of perceived organizational support and job satisfaction on work engagement at PT. X. PT. X is a company that provides services in the field of construction vendors. Services provided include providing construction manufacturing and installation services for events organized by companies, agencies and organizations such as the manufacture and installation of booths, stages, and event organizing needs. Respondents in this study were 75 employees of PT. X. The sampling technique used is total sampling. The data analysis technique used is multiple regression. The results showed that the R Square value was 0,938, so that the influence of perceived organizational support and job satisfaction on work engagement was 93,8%, where the remaining 6,2% was influenced by other factors outside of this study, such as organizational commitment, individual intention to leave the organization, characteristics personality, compensation, company culture, communication with colleagues, peer support, leadership style, and type of work performed.